Effective Safety Communication Strategies to Reduce Workplace Accidents in High-Risk Industries - Hanifah Handayani (Jurnal Ragam Pengabdian, 2026)
Occupational Health and Safety (OHS) is a crucial issue in high-risk industries due to the high potential for work accidents that impact worker productivity and welfare. One of the important factors that affect the effectiveness of OHS implementation is the quality of safety communication in the work environment. This study aims to analyze the influence of safety communication strategies on work safety behavior and understand safety communication practices and barriers at the operational level. The research uses a mixed methods approach with a sequential explanatory design. Quantitative data was collected through a survey of 55 purposively selected production workers, then analyzed using regression analysis to test the relationship between variables. Furthermore, qualitative data were obtained through in-depth interviews with 4 key informants consisting of production workers, supervisors, and OHS officers, which were analyzed using thematic analysis to explain the quantitative findings. This research was carried out in a high-risk industry located in Subang Regency, West Java, as one of the industrial estates with intensive operational activities. The results showed that message clarity, consistency of delivery, and two-way communication in safety communication strategies had a significant effect on improving safe work behavior and reducing the risk of work accidents. Qualitative findings reveal that time constraints, differences in worker understanding, and dominance of one-way communication are the main challenges in the implementation of safety communication. This study concludes that strengthening participatory and contextual safety communication strategies is a key element in increasing the effectiveness of OHS implementation, as well as making a practical contribution to the development of occupational safety policies and programs in the industrial sector